The emergence and evolution of infant externalizing behavior. (August 2015) - Lorber, Michael F.; Del Vecchio, Tamara; Slep, Amy M. Smith
Abstract: In the present investigation, we examined the developmental viability of the externalizing behavior construct spanning the period from 8 to 24 months of age. A sample of 274 psychologically aggressive couples was recruited from hospital maternity wards and followed from childbirth through 24 months of age. Mothers and fathers completed questionnaire measures of infant physical aggression, defiance, activity level, and distress to limitations at 8, 15, and 24 months. The developmental viability of externalizing behavior at each age studied was suggested by several results. Physical aggression, defiance, activity level, and distress to limitations reflected the operation of a single underlying externalizing behavior factor. In some cases, these individual facets of externalizing behavior became more strongly associated with one another over time. The externalizing construct exhibited remarkable longitudinal stability, with the stability of physical aggression and defiance increasing with age. The externalizing behavior construct was concurrently and prospectively associated with several factors in its nomological network (e.g., interparental conflict and poor parental bond with the infant). Our findings suggest that externalizing behaviors coalesce into a psychologically meaningful construct by 8 months of infant life. Researchers who seek to chart the emergence of the externalizing behavior construct may now need to look to earlier months.